2001
DOI: 10.1053/seiz.2000.0511
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective properties of the novel antiepileptic drug levetiracetam in the rat middle cerebral artery occlusion model of focal cerebral ischemia

Abstract: Levetiracetam (LEV) is a new antiepileptic drug with a promising preclinical profile involving both anticonvulsant and antiepileptogenic effects in kindling models. The latter stimulated the present study to compare its neuroprotective properties with the potent and selective, non-competitive NMDA antagonist, MK-801, in the rat middle cerebral artery occlusion model. Twenty-four hours after a transient occlusion of 90 minutes the animals were sacrificed and infarct volume and lesion distribution were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 21 publications
1
61
1
1
Order By: Relevance
“…22,23 The lack of neuroprotective effect by LEV is rather surprising. It has been shown, in fact, that this drug reduces the ischemia-induced brain damage in vivo 24 and is neuroprotective against kainate-induced toxicity. 25 Moreover, the present study, as well as previous works, 26,27 has shown that LEV reduces HVA Ca 2ϩ currents, one of the major target of putative neuroprotective therapies.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The lack of neuroprotective effect by LEV is rather surprising. It has been shown, in fact, that this drug reduces the ischemia-induced brain damage in vivo 24 and is neuroprotective against kainate-induced toxicity. 25 Moreover, the present study, as well as previous works, 26,27 has shown that LEV reduces HVA Ca 2ϩ currents, one of the major target of putative neuroprotective therapies.…”
Section: Discussionmentioning
confidence: 99%
“…80,81 As demonstrated in laboratory animal studies of focal and global ischemia, antiepileptic drugs may also act as neuroprotectants. 82 For example, phenytoin, 83 benzodiazepines, 84 lamotrigine, [85][86][87][88] topiramate, 89 -91 levetiracetam, 92 and zonisamide 93 have neuroprotective properties and might, therefore, have beneficial effects when used to treat seizures in the setting of hyperacute stroke. However, there remain no clinical data proving this to be true, and the comparative risks and benefits of the different antiepileptic drugs have not been well studied in stroke patients.…”
Section: Treatmentmentioning
confidence: 99%
“…Histopathological changes were not observed in Group Piracetam, a nootropic drug, has been already used for neurological, neuropsychiatrical, and neurosurgerical disorders (6,7,(16)(17)(18). In conclusion, piracetam therapy increased antioxidant activity and decreased oxidative stress scores in testicular samples.…”
Section: Histological Resultsmentioning
confidence: 79%
“…Piracetam is a nootropic agent used in neurological sciences because of its rheological, anti-thrombotic, and neuro-protective properties (6). After proving of its influence on improving micro-circulation, the area of usage for this drug extended (7).…”
Section: Introductionmentioning
confidence: 99%